2023
DOI: 10.1002/smll.202206949
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure‐Dependent Water‐Dissociation Pathways of Ruthenium‐Based Catalysts in Alkaline H2‐Evolution

Abstract: current conditions of electrocatalytic water splitting mainly include acidic and basic media. [5][6][7][8] When considering the huge difficulty in producing affordable acidic oxygen evolution electrodes in water splitting, the electrocatalytic water splitting in alkaline environments has become a meaningful strategy to produce H 2 on a large scale, [9][10][11][12][13] while the commercial alkaline hydrogen evolution reaction (HER) catalyst still relies on the metallic platinum (Pt), which confronts with slow w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…It has been reported that SCN − of potassium thiocyanate (KSCN) adsorb on the surface of both Ru nanocluster and Ru SAs while ethylene diamine tetra acetic acid (EDTA) mainly forms coordination bonds with Ru SAs. [31,32] With the addition of EDTA (10 mm) or KSCN (10 mm), the current density of β-Ni(OH) 2 /Ni-Ru SAs NSAs decreases more significantly in EDTA, due to the suppression of Ru SA sites by EDTA, thus demonstrating the important role of Ru SAs in the catalytic HER process. As the concentration of Ru clusters in β-Ni(OH) 2 /Ni-Ru SAs NSAs is only ≈10%, we think that the main active sites for HER are Ru SAs.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that SCN − of potassium thiocyanate (KSCN) adsorb on the surface of both Ru nanocluster and Ru SAs while ethylene diamine tetra acetic acid (EDTA) mainly forms coordination bonds with Ru SAs. [31,32] With the addition of EDTA (10 mm) or KSCN (10 mm), the current density of β-Ni(OH) 2 /Ni-Ru SAs NSAs decreases more significantly in EDTA, due to the suppression of Ru SA sites by EDTA, thus demonstrating the important role of Ru SAs in the catalytic HER process. As the concentration of Ru clusters in β-Ni(OH) 2 /Ni-Ru SAs NSAs is only ≈10%, we think that the main active sites for HER are Ru SAs.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that SCN − ions and EDTA could strongly bind to metal−N sites, which would block that metal site for O 2 adsorption, resulting in attenuated O 2 reduction activity. 44,55,56 As displayed in Figures 3d and S17, a distinct declining ORR activity for both InPc and InPPc can be observed after addition of SCN − , which can be ascribed to the blocking of the In−N active site by SCN − . 7,44,57 As shown in Figure S18, when EDTA was added, the performance of the catalyst became worse and the selectivity of H 2 O 2 decreased sharply.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 88%
“…The semicircular shape of the electrochemical impedance spectroscopy results (Figure S16) showed that the InPPc had a smaller charge transfer resistance compared to InPc at different overpotentials, suggesting the faster charge transfer rate in the 2e – ORR process. ,, To unveil the active sites of InPc and InPPc for 2e – ORR, poisoning experiments were also conducted in 0.1 M KOH electrolyte with or without addition of potassium thiocyanate (KSCN) and ethylene diamine tetraacetic acid (EDTA). It is known that SCN – ions and EDTA could strongly bind to metal–N sites, which would block that metal site for O 2 adsorption, resulting in attenuated O 2 reduction activity. ,, As displayed in Figures d and S17, a distinct declining ORR activity for both InPc and InPPc can be observed after addition of SCN – , which can be ascribed to the blocking of the In–N active site by SCN – . ,, As shown in Figure S18, when EDTA was added, the performance of the catalyst became worse and the selectivity of H 2 O 2 decreased sharply. These results verify that the In–N sites are mainly responsible for the 2e – ORR activity.…”
mentioning
confidence: 99%
“…Yang et al utilized DFT calculations and experimental operations to systematically reveal the unique delocalization-localization coexistence at the interface of Ru nanoclusters and Ru single-atom. [80] By analyzing the adsorption and desorption behavior of different intermediates during HER, the authors discovered that the delocalized electrons in Ru nanoclusters delivered a stronger ability to adsorb OH*, and the localized electrons in single atom Ru were more inclined to adsorb H*. As depicted in Figure 10a, the active centers delivered Reproduced with permission.…”
Section: Inter-substep Synergymentioning
confidence: 99%